PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN MINAT BELAJAR IPA PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS IV SD NEGERI SERDANG 2 - Rian Azhar Ramadhan; Henny Setiani; Lailatul Azkia; Aliyah (STKIP Subang, 2025)
This study aims to explore the application of the Problem Based Learning (PBL) Model in Natural Science (IPA) learning, especially on the human digestive system material, and to measure its impact on the learning interest of fourth grade students of SD Negeri Serdang 2. The method used is quantitative with a pre-experimental one group pretest posttest design. The study involved 30 students with a saturation sampling technique, where all members of the population were sampled. Data were collected through pretest and posttest, as well as observation sheets to assess student learning activities. The results showed a significant increase in students' learning interest, involvement, participation, and discussion skills after the implementation of the PBL model, with p values ​​of 0.001, 0.002, 0.003, and 0.004, respectively. These findings indicate that the implementation of the PBL model has succeeded in increasing students' learning interest and activities.